High-purity silicon carbide ceramic as well as preparation method and application thereof
By using β-SiC micropowder and oscillation pressure sintering technology, high-purity and high-density silicon carbide ceramics are prepared, which solves the problem of insufficient purity and density of silicon carbide ceramics in the prior art, and achieves high-performance ceramic materials that meet the needs of the semiconductor field.
Patent Information
- Application Number
- CN202510390955.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2025-06-17
AI Technical Summary
The prior art is difficult to prepare high-purity and high-density silicon carbide ceramics, and cannot meet the requirements of the purity and density of silicon carbide ceramics in the semiconductor field.
β-SiC powder is used as raw material, and high-purity silicon carbide ceramics are prepared by spray granulation, dry press molding or isostatic press molding, combined with oscillation pressure sintering technology. During the oscillation pressure sintering process, an oscillation pressure and frequency are applied to promote the phase transition from β-SiC to 4H-SiC and improve the density of the material.
The preparation of silicon carbide ceramics with high purity (99.999%) and high density (not less than 3.076g/cm3) has been achieved, with a porosity of less than 3.79% and a bending strength of more than 416MPa, meeting the high temperature usage requirements of semiconductor equipment.
Smart Images

Figure CN120157485A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of high-purity ceramic preparation, and particularly relates to a high-purity silicon carbide ceramic, a preparation method thereof, and an application thereof. Background Art
[0002] Silicon carbide has become one of the preferred materials in the high-tech field in recent years due to its excellent properties such as oxidation resistance, high high-temperature strength, good wear resistance, good thermal stability, small thermal expansion coefficient, large thermal conductivity, high hardness and elastic modulus, good thermal shock resistance, good corrosion resistance, good specific stiffness, and good optical processing performance. In the semiconductor field, silicon carbide ceramics are used in many projects, such as oxidation furnaces, diffusion furnaces, lithography machines and other semiconductor equipment, and high-purity silicon carbide materials have been widely used abroad to replace traditional quartz glass.
[0003] Silicon carbide ceramic is a material with strong covalent bonds, and its diffusion rate during sintering is very low; at a high temperature of 2100 °C, the self-diffusion coefficients of carbon (C) and silicon (Si) are 1.5×10 -10 cm 2 / s and 2.5×10 -13 cm 2 / s respectively; at the same time, during the sintering process of silicon carbide (SiC), due to strong unidirectional bonding and evaporation-condensation gas-phase migration incentives, only necks can be formed between adjacent SiC particles, and diffusion migration cannot occur; therefore, SiC without adding sintering aids cannot be sintered densely.
[0004] In the semiconductor field, silicon carbide ceramic components require both high density and high purity. However, the purity of the silicon carbide ceramics prepared by the existing technology is relatively low and cannot meet the requirements for the purity of silicon carbide ceramics in the semiconductor field; in addition, the residual silicon in the prepared silicon carbide ceramics also reduces the use temperature of the silicon carbide ceramics. Therefore, there is an urgent need to develop a preparation method for silicon carbide ceramics with both high purity and high density. Summary of the Invention
[0005] Aiming at the deficiencies of the existing technology, the present invention publicly proposes a high-purity silicon carbide ceramic, a preparation method thereof, and an application thereof, so as to solve or at least alleviate one or more of the above problems and other problems existing in the existing technology.
[0006] The present invention discloses a preparation method for a high-purity silicon carbide ceramic, comprising the following steps:
[0007] S1. Using silicon carbide micropowder as a raw material, the crystal form of the silicon carbide micropowder is β-SiC, and its purity is not less than 99.999%.
[0008] S2. Add silicon carbide micropowder, distilled water, dispersant and binder into a blender and stir to prepare a slurry;
[0009] S3. Transport the prepared slurry to a spray granulation tower and obtain granulated powder through the spray granulation tower;
[0010] S4. Sieve the granulated powder through a 100-mesh sieve, and then age the sieved granulated powder for 72 h;
[0011] S5. Form the aged granulated powder into a green body by dry pressing or isostatic pressing;
[0012] S6. Load the green body into a graphite mold, and then place the graphite mold in an oscillating pressure sintering furnace for vacuum sintering, and obtain silicon carbide ceramics after cooling with the furnace;
[0013] Preferably, in the step S6, the vacuum sintering process of the oscillating pressure sintering furnace includes the following steps:
[0014] S601: The heating rate V1 is 15-20 °C / min, the sintering pressure F is 30-50 MPa, and heat up to 1600 °C;
[0015] S602: The heating rate V2 is 10-20 °C / min, heat up to T of 1750-1850 °C, and keep the temperature for t of 0.5-2 h; meanwhile, apply an oscillating pressure with an amplitude A of 10-20 MPa on the basis of the sintering pressure F of 30-50 MPa, and the frequency f is 10-20 Hz.
[0016] Preferably, the amplitude A is 10-15 MPa.
[0017] Preferably, the frequency f is 10-15 Hz.
[0018] Preferably, in the step S2, the mass ratio a of the silicon carbide micropowder to the distilled water is 1:(1-1.2).
[0019] Preferably, in the step S2, the addition ratio b of the dispersant is 0.1-0.2% of the mass of the silicon carbide micropowder.
[0020] Preferably, in the step S2, the addition ratio c of the binder is 4.0-5.0% of the mass of the silicon carbide micropowder.
[0021] Preferably, in the step S3, the inlet and outlet temperatures of the spray granulation tower are 180 °C and 60 °C respectively, the slurry feeding speed is 65 r / min, and the nozzle rotation frequency is 1800 Hz.
[0022] In addition, the present invention provides the high-purity silicon carbide ceramics prepared by the preparation method of the high-purity silicon carbide ceramics described above.
[0023] Furthermore, the present invention provides the application of the above-mentioned high-purity silicon carbide ceramic in semiconductor devices. In particular, the application of the furnace lining prepared from high-purity silicon carbide ceramic in semiconductor devices such as oxidation furnaces and diffusion furnaces, and the application of the precision ceramic components prepared from high-purity silicon carbide ceramic in lithography machines.
[0024] The present invention has the following beneficial effects:
[0025] This technical solution provides a preparation method of high-purity silicon carbide ceramic. The present invention uses β-SiC as the raw material without introducing other raw materials, and sequentially prepares silicon carbide ceramic through granulation, forming and sintering, effectively improving the purity; during the sintering process, by adding an oscillating pressure with an amplitude A of 10-20 MPa and a frequency f of 10-20 Hz, more β-SiC is transformed into 4H-SiC, generating volume expansion through phase transformation, increasing the system energy, and promoting the particle migration and rearrangement process, thereby realizing the densification of silicon carbide ceramic and achieving high density; finally, high-purity and high-density silicon carbide ceramic is prepared by the oscillating pressure sintering technology. The purity of the silicon carbide ceramic reaches 99.999%, the density is not lower than 3.076 g / cm 3 , the porosity is lower than 3.79%, and the flexural strength is higher than 416 MPa. Description of the Drawings
[0026] In order to more clearly illustrate the specific embodiments of the present disclosure, the drawings required for the specific embodiments will be briefly introduced below. In all the drawings, the components or parts do not necessarily draw according to the actual scale.
[0027] Figure 1 XRD diagrams of the silicon carbide ceramics prepared in Example 1 and Comparative Examples 1-9 of the present invention. Specific Embodiments
[0028] The embodiments of the technical solutions of the present disclosure will be described in detail below with reference to the drawings. The following embodiments are only used to more clearly illustrate the technical solutions of the present disclosure, so they are only examples and cannot be used to limit the protection scope of the present disclosure.
[0029] It should be noted that unless otherwise specified, the technical terms or scientific terms used in this application should be the ordinary meanings understood by those skilled in the art to which the present invention belongs.
[0030] In the description of the present application, it should be understood that the orientation or positional relationship indicated by the terms "center", "longitudinal", "transverse", "length", "width", "thickness", "upper", "lower", "front", "rear", "left", "right", "vertical", "horizontal", "top", "bottom", "inner", "outer", "clockwise", "counterclockwise", "axial", "radial", "circumferential", etc. is based on the orientation or positional relationship shown in the drawings. It is only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation. Therefore, it should not be construed as a limitation to the present invention.
[0031] In addition, the terms "first", "second", etc. are only used for descriptive purposes and cannot be understood as indicating or implying relative importance or implicitly specifying the quantity of the indicated technical features. In the description of the present invention, the meaning of "a plurality" is two or more unless otherwise specifically defined.
[0032] In the present application, unless otherwise clearly specified and limited, the terms "mounted", "connected", "connected to", "fixed", etc. shall be construed in a broad sense. For example, it may be a fixed connection, a detachable connection, or integrated; it may be a mechanical connection or an electrical connection; it may be directly connected or indirectly connected through an intermediate medium, and it may be the internal communication of two elements or the interaction relationship between two elements. For those of ordinary skill in the art, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0033] In the present application, unless otherwise clearly specified and limited, the first feature being "on" or "under" the second feature may be that the first and second features are in direct contact, or the first and second features are indirectly in contact through an intermediate medium. Moreover, the first feature being "above", "over" and "on top of" the second feature may be that the first feature is directly above or obliquely above the second feature, or merely indicates that the first feature has a higher horizontal height than the second feature. The first feature being "under", "beneath" and "underneath" the second feature may be that the first feature is directly below or obliquely below the second feature, or merely indicates that the first feature has a lower horizontal height than the second feature.
[0034] In Examples 1-7 and Comparative Examples 1-9 of the present invention, a method for preparing high-purity silicon carbide ceramics is provided, and the specific parameters of the preparation process of the high-purity silicon carbide ceramics are shown in Table 1.
[0035] A method for preparing high-purity silicon carbide ceramics, comprising:
[0036] S1. Use silicon carbide micropowder as the raw material. The crystal form of the silicon carbide micropowder is β-SiC, and its purity is not less than 99.999%. The silicon carbide micropowder of this crystal form has good sphericity and high fluidity, and the activity of the silicon carbide micropowder of this crystal form is extremely high, which is beneficial to sintering densification;
[0037] S2. Add silicon carbide micropowder, distilled water, dispersant and binder into a blender and stir to prepare a slurry; the stirring frequency is 30 - 40 Hz, and the stirring time is 24 - 36 h; among them, the mass ratio a of silicon carbide micropowder to distilled water is 1:(1 - 1.2); the addition ratio b of the dispersant is 0.1 - 0.2% of the mass of the silicon carbide micropowder, and the addition ratio c of the binder is 4.0 - 5.0% of the mass of the silicon carbide micropowder;
[0038] S3. Transport the prepared slurry to a spray granulation tower to obtain granulated powder through the spray granulation tower; among them, the inlet and outlet temperatures of the spray granulation tower are 180°C and 60°C respectively, the slurry feeding speed is 65 r / min, and the nozzle rotation frequency is 1800 Hz;
[0039] S4. Sieve the granulated powder through a 100-mesh sieve, and then age the sieved granulated powder for 72 h;
[0040] S5. Form the aged granulated powder into a green body by dry pressing or isostatic pressing;
[0041] S6. Load the green body into a graphite mold, and then place the graphite mold in an oscillating pressure sintering furnace for vacuum sintering, and obtain silicon carbide ceramics after cooling with the furnace; among them, the vacuum sintering process of the oscillating pressure sintering furnace includes the following steps:
[0042] S601: The heating rate V1 is 15 - 20°C / min, the sintering pressure F is 30 - 50 MPa, and heat up to 1600°C;
[0043] S602: The heating rate V2 is 10 - 20°C / min, heat up to T = 1750 - 1850°C, and keep warm for t = 0.5 - 3 h; meanwhile, on the basis of the sintering pressure F of 30 - 50 MPa, apply an oscillating pressure with an amplitude A of 0 - 30 Mpa and a frequency f of 5 - 30 Hz. In this step S602, heating up and applying the oscillating pressure with amplitude A are carried out synchronously, that is, an oscillating pressure with amplitude A is added in both the two stages of heating up to the target temperature at V2 and keeping warm at the target temperature; specifically, the oscillating pressure with an amplitude A of 0 - 30 Mpa and a frequency f of 5 - 30 Hz.
[0044] In step S3, the prepared slurry can also be poured into a tray, and then the tray is placed in an oven for drying and cooled to room temperature. After that, the material block in the tray is taken out and crushed to obtain granulated powder. The drying temperature of the oven is 80 °C, the drying time is 2.0 - 4.0 h, and the moisture content of the material block in the tray after drying is not higher than 3%.
[0045] Among them, in different tests and actual production, the mass ratio a of silicon carbide micropowder to distilled water can be 1:(1 - 1.2). The addition ratio b of the dispersant can be 0.1 - 0.2% of the mass of the silicon carbide micropowder, and the dispersant can be selected from one of polyacrylamide, polymethacrylic acid, carboxymethyl cellulose, polyacrylic acid, polyvinyl alcohol, and oleic acid. The addition ratio c of the binder can be 4.0 - 5.0% of the mass of the silicon carbide micropowder, and the binder can be selected from one of phenolic resin, epoxy resin, methyl cellulose, carboxymethyl cellulose, polyethylene, and carboxypropyl methyl cellulose. The stirring frequency can be 30 - 40 Hz, and the stirring time can be 24 - 36 h. The mass ratio a of β-SiC micropowder to distilled water can be 1:(1 - 1.2), and preferably the mass ratio a of β-SiC micropowder to distilled water is 1:1. During the sintering process, the heating rate V1 can be 15 - 20 °C / min, and preferably V1 is 15 °C / min; the sintering pressure F can be 30 - 50 MPa, and preferably F is 40 MPa; the heating rate V2 can be 10 - 20 °C / min, and preferably V2 is 10 °C / min; the temperature is raised to T which can be 1750 - 1850 °C, and preferably T is 1800 °C. In step S602, it is applied based on the sintering pressure F of 30 - 50 MPa; the amplitude A can be 10 - 20 MPa, and preferably A is 15 MPa; the frequency f can be 10 - 20 Hz, and preferably f is 15 MPa.
[0046] Comparative Example 10
[0047] The raw material used is a-SiC micropowder, and the rest of the preparation process is the same as that of Example 1.
[0048] In step S5, dry pressing or isostatic pressing can be used for green body preparation; in Examples 1 - 7 and Comparative Examples 1 - 10, isostatic pressing is used for green body preparation.
[0049] Table 1
[0050]
[0051]
[0052] Performance Test
[0053] Test Standard:
[0054] (1) The purity is tested by a glow discharge mass spectrometer.
[0055] (2) The density shall be measured in accordance with the national standard "Test Methods for Density and Apparent Porosity of Fine Ceramics GB / T 25995—2010".
[0056] (3) The porosity shall be measured in accordance with the national standard "Test Methods for Density and Apparent Porosity of Fine Ceramics GB / T 25995—2010".
[0057] (4) The flexural strength shall be tested by the three-point bending method.
[0058] Test results: The performance test results are shown in Table 2.
[0059] Table 2
[0060]
[0061]
[0062] From the comparative analysis of Examples 1-7, it can be seen that the purity of the silicon carbide ceramics prepared according to the present invention exceeds 99.999%, the density is not less than 3.076 g / cm 3 , the porosity is lower than 3.79%, the flexural strength is higher than 416 MPa, and the highest flexural strength can reach 425 MPa. Moreover, there is no residual silicon in the silicon carbide ceramics prepared using β-SiC as the raw material, ensuring that the silicon carbide ceramic products have excellent purity, and their service temperature can reach 1650 °C; the service temperature of the silicon carbide ceramic products containing residual silicon cannot be higher than 1400 °C. If the working condition exceeds 1400 °C, the silicon carbide ceramic products containing residual silicon cannot be used normally.
[0063] Currently, the prior art records that when β-SiC exceeds 1600 °C during sintering, a phase transformation will occur, that is, β-SiC gradually transforms into α-SiC. The crystal forms of α-SiC include 6H-SiC and 4H-SiC; the crystal form transformation will cause volume expansion. The volume expansion from β-SiC to 6H-SiC is 1.73 times, and the volume expansion from β-SiC to 4H-SiC is 1.86 times. During sintering, as the phase change amount of β-SiC increases, the thermal stress generated by the volume expansion after the phase change causes the energy of the system (including thermal energy, internal energy, surface energy, elastic energy, etc.) to increase, promoting the process of particle migration and rearrangement, thereby promoting the densification of the sintered silicon carbide.
[0064] Such as Figure 1As shown, through the comparative analysis of Example 1 and Comparative Examples 1-2, it can be seen that when the frequency after applying the amplitude is relatively low, due to the incomplete bonding between grains, the porosity is relatively high and the density is relatively low. This is because when the frequency is relatively low, more β-SiC transforms into 6H-SiC, and very few or no β-SiC transforms into 4H-SiC, resulting in an increase in porosity and a decrease in the flexural strength. When the frequency after applying the amplitude is relatively high, although it ensures that more β-SiC transforms into 4H-SiC, but the too high frequency causes the grains to move too violently, so that some gases are wrapped inside the material before they can be discharged, forming pores, which instead increases the porosity, reduces the densification degree of the material, and leads to a decrease in density. The increase in porosity and the decrease in density will lead to a decrease in the strength of the material. At the same time, the internal stress generated at too high a frequency may exceed the bearing limit of the material, causing defects such as microcracks to appear in the silicon carbide ceramic material, further weakening the strength of the material.
[0065] As Figure 1 shown, through the comparative analysis of Example 1 and Comparative Examples 3-4, it can be seen that when the applied amplitude is relatively low, the porosity increases and the density decreases. When the amplitude is relatively low, more β-SiC transforms into 6H-SiC, and a small amount of β-SiC transforms into 4H-SiC. When the applied amplitude is relatively high, the content of β-SiC transformed into 4H-SiC increases. The transformation of β-SiC into 4H-SiC produces a volume expansion of 1.86 times, forming thermal stress inside the structure, accelerating the grain growth, and promoting densification. When the amplitude is relatively high, the transformation amount of 4H-SiC increases, the movement between grains intensifies, and the grains grow excessively, resulting in an increase in the porosity of the ceramic, a decrease in density, and a decrease in strength.
[0066] As Figure 1As shown, through the comparative analysis of Example 1 and Comparative Example 5, it can be seen that when both the applied amplitude and frequency are relatively low, there are no peaks of 4H-SiC at 2θ of 33.44°, 34.6° and 57.16°, indicating that the transformation amount of β-SiC to 4H-SiC has decreased; the peaks at 2θ of 34°, 41.28° and 54.52° are significantly increased, indicating that more β-SiC has transformed into 6H-SiC; this leads to an increase in porosity, a decrease in density and a decrease in flexural strength. Through the comparative analysis of Example 1 and Comparative Example 6, it can be seen that when the applied amplitude is 0, no peaks of 4H-SiC are detected at 2θ of 33.44°, 34.6° and 57.16°, and at the same time, it is observed that the peaks at 2θ of 34°, 41.28° and 54.52° are significantly increased, indicating that more β-SiC has transformed into 6H-SiC, resulting in an increase in porosity, a decrease in density and a decrease in flexural strength. Through the comparative analysis of Example 1 and Comparative Example 7, it can be seen that when both the applied amplitude and frequency are relatively high, it ensures that more β-SiC transforms into 4H-SiC. Although the density and porosity do not decrease significantly, the flexural strength decreases significantly; this is because when the amplitude and frequency are too high, the grains of silicon carbide grow rapidly during the sintering process, resulting in a decrease in the flexural strength of silicon carbide after sintering.
[0067] As Figure 1 shown, through the comparative analysis of Example 1 and Comparative Examples 8-9, it can be seen that when the holding time is too low, β-SiC does not have enough time to transform into more 4H-SiC, resulting in a large porosity, thereby reducing the density and flexural strength; when the holding time is too long, after β-SiC transforms into α-SiC, the grains of silicon carbide will grow rapidly. Although the density does not decrease significantly and the porosity does not increase significantly, the flexural strength of silicon carbide decreases significantly.
[0068] From the comparative analysis of Example 1 and Comparative Example 10, it can be seen that although using α-SiC as the raw material significantly improves the purity compared with the prior art, the prepared silicon carbide is not ideal in terms of density, porosity, and flexural strength. β-SiC has a cubic crystal system (3C-SiC) structure, with a more uniform atomic arrangement, lower lattice energy, and a faster atomic diffusion rate during sintering, which is conducive to densification. α-SiC has a hexagonal crystal system (such as 4H-SiC or 6H-SiC) structure, with a relatively complex atomic arrangement, higher lattice energy, and a slower atomic diffusion rate during sintering, making densification more difficult. The phase transformation of β-SiC to α-SiC during sintering, which is usually accompanied by grain refinement and homogenization, helps to improve the mechanical properties of the material. There are fewer phase transformations during the sintering of α-SiC, and grain growth is likely to get out of control, resulting in a decline in material properties. Due to its cubic structure, high sintering activity, and smaller grain size, β-SiC is more easily densified during sintering, thus obtaining a higher density, lower porosity, and higher flexural strength. However, due to the complexity of the hexagonal structure and lower sintering activity of α-SiC, densification is more difficult, resulting in relatively poor material properties. Therefore, β-SiC has significant advantages as a raw material in the preparation of high-performance silicon carbide ceramics.
[0069] The above embodiments are only used to illustrate the technical solutions of the present disclosure, and are not intended to limit them; although the present disclosure has been described in detail with reference to the foregoing embodiments, those of ordinary skill in the art should understand that they can still modify the technical solutions described in the foregoing embodiments, or perform equivalent replacements on some or all of the technical features; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present disclosure, and they should all be covered by the scope of the claims and the specification of the present disclosure.
Claims
1. A method for preparing high-purity silicon carbide ceramics, characterized in that: The steps include: S1. Silicon carbide powder is used as raw material. The crystal form of silicon carbide powder is β-SiC and its purity is not less than 99.999%; S2, adding silicon carbide powder, distilled water, dispersant and binder into a mixer and stirring to prepare a slurry; S3, conveying the prepared slurry to a spray granulation tower, and obtaining granulated powder through the spray granulation tower; S4, sieving the granulated powder through a 100-mesh sieve, and then aging the sieved granulated powder for 72 hours; S5, forming a green body by dry pressing or isostatic pressing the aged granulated powder; S6. Loading the green body into a graphite mold, placing the graphite mold in an oscillating pressure sintering furnace for vacuum sintering, and obtaining silicon carbide ceramics after cooling in the furnace.
2. The method for preparing high-purity silicon carbide ceramics according to claim 1, characterized in that: In step S6, the vacuum sintering process in the oscillating pressure sintering furnace includes the following steps: S601: Heating rate V1 is 15-20℃ / min, sintering pressure F is 30-50MPa, and the temperature is raised to 1600℃; S602: The heating rate V2 is 10-20℃ / min, the temperature is raised to T of 1750-1850℃, and the heat preservation t is 0.5-2h; at the same time, an oscillating pressure with an amplitude A of 10-20MPa and a frequency f of 10-20Hz is applied on the basis of a sintering pressure F of 30-50MPa.
3. The method for preparing high-purity silicon carbide ceramics according to claim 2, characterized in that: The amplitude A is 10-15 MPa.
4. The method for preparing high-purity silicon carbide ceramics according to claim 2, characterized in that: The frequency f is 10-15 Hz.
5. The method for preparing high-purity silicon carbide ceramics according to claim 1, characterized in that: In the step S2, the mass ratio a of silicon carbide powder to distilled water is 1:(1-1.2).
6. The method for preparing high-purity silicon carbide ceramics according to claim 1, characterized in that: In the step S2, the addition ratio b of the dispersant is 0.1-0.2% of the mass of the silicon carbide powder.
7. The method for preparing high-purity silicon carbide ceramics according to claim 1, characterized in that: In the step S2, the addition ratio c of the binder is 4.0-5.0% of the mass of the silicon carbide powder.
8. The method for preparing high-purity silicon carbide ceramics according to claim 1, characterized in that: In step S3, the inlet and outlet temperatures of the spray granulation tower are 180° C. and 60° C. respectively, the slurry feeding speed is 65 r / min, and the nozzle rotation frequency is 1800 Hz.
9. A high-purity silicon carbide ceramic prepared by the method for preparing a high-purity silicon carbide ceramic according to any one of claims 1 to 8.
10. Use of the high-purity silicon carbide ceramic according to claim 9 in semiconductor devices.